Sex Hormones in Allergic Conjunctivitis: Altered Levels of Circulating Androgens and Estrogens in Children and Adolescents with Vernal Keratoconjunctivitis - Marta Sacchetti; Alessandro Lambiase; Costanzo Moretti; Flavio Mantelli; Stefano Bonini (Journal of Immunology Research)
Purpose. Vernal keratoconjunctivitis (VKC) is a chronic allergic disease mainly affecting boys in prepubertal age and usually recovering after puberty. To evaluate a possible role of sex hormones in VKC, serum levels of sex hormones in children and adolescents with VKC were assessed. Methods. 12 prepubertal and 7 early pubertal boys with active VKC and 6 male patients with VKC in remission phase at late pubertal age and 48 healthy age and sex-matched subjects were included. Serum concentration of estrone, 17 beta-estradiol, dehydroepiandrosterone-sulfate, total testosterone and free testosterone, dihydrotestosterone (DHT), cortisol, delta-4-androstenedione, follicle-stimulating hormone, luteinizing hormone, and sex-hormones binding globuline (SHBG) were evaluated. Results. Serum levels of Estrone were significantly increased in all groups of patients with VKC when compared to healthy controls (P<0.001). Prepubertal and early pubertal VKC showed a significant decrease in DHT (P=0.007 and P=0.028, resp.) and SHBG (P=0.01 and P=0.002, resp.) when compared to controls and serum levels of SHBG were increased in late pubertal VKC in remission phase (P=0.007). Conclusions and Relevance. VKC patients have different circulating sex hormone levels in different phases of the disease and when compared to nonallergic subjects. These findings suggest a role played by sex hormones in the pathogenesis and/or activity of VKC.